Complement-independent dengue virus type 1 infection-enhancing antibody reduces complement-dependent and -independent neutralizing antibody activity - Atsushi Yamanaka (2018)
© 2016 Elsevier Ltd Dengue fever and dengue hemorrhagic fever are globally important mosquito-transmitted viral diseases. However, the only licensed vaccine is not highly protective. Viremia is related to disease severity in infected humans, and it is thought to be reduced by neutralizing antibodies but increased by infection-enhancing antibodies. We established an assay system to measure the balance between neutralizing and enhancing antibodies and found that most dengue-immune individuals in endemic areas carry complement-independent enhancing antibodies (CiEAb). Studying CiEAb is important for dengue vaccine development because the enhancing activity of CiEAb does not decrease in the presence of complement, which can reduce the enhancing activity of other antibodies in vitro. Here, we investigated the effects of CiEAb on the activity of neutralizing antibodies (mainly, complement-dependent neutralizing antibodies; CdNAb) using cocktails of mouse monoclonal antibodies (MAbs) against dengue virus type 1 (DENV-1). These cocktails included MAbs with enhancing activity only (represented by D1-V-3H12 [3H12]) or neutralizing activity only (represented by D1-IV-7F4 [7F4]). Because 3H12, an IgG1 subclass antibody, is complement-independent and cross-reacted with all dengue serotypes, it is a suitable model of CiEAb. An approximately equal amount of 3H12 abolished the neutralizing activity of 7F4. The complement-dependent neutralizing activities of the IgG2a and IgG2b variants of 7F4 were also completely inhibited by ⩾3-fold concentrations of the IgG1 variant. The complement-dependent antibody activities of other anti-DENV-1 MAbs and those of MAbs directed against other serotypes were inhibited 50% by 3H12 at various mixing ratios, ranging from one-hundredth to 10-fold. The complement-dependent neutralizing activities of dengue-immune mouse ascites fluids were also effectively inhibited by 3H12. This suggests that concomitantly induced CiEAb exerts an unwanted effect on the protective capacity of a vaccine. Thus, the effective inhibition of the neutralizing activity of CdNAb by CiEAb has implications for dengue pathogenesis and vaccine development.